UJI KIMIA, FISIK DAN BIOLOGI PAKAN MANDIRI DENGAN PEMANFAATAN BAHAN BAKU LOKAL DI BALAI PERIKANAN BUDIDAYA AIR TAWAR (BPBAT) TATELU MINAHASA UTARA - Siti Aisyah Saridu; Budiyati Budiyati; Yunus Anugrah Sani; Supryady Supryady; Muhammad Hery Riyadi Alauddin; Ihwan Ihwan (Universitas Mataram, 2024)
Feed is one of the components in fish farming activities that will affect the growth and survival of fish. The cost allocation required for feed procurement reaches 60-70% of the total production cost, so alternatives are needed to provide cheaper feed, one of which namely self-made feed using local raw materials. The purpose of this study was to test the physical (buoyancy, durability, homogeneity level, hardness level), chemical (protein, carbohydrates, fats, water, and ash), and biological (absolute weight gain, FCR, EPP) qualities. The data obtained were analyzed using quantitative descriptive analysis methods. The results of the physical test of the feed showed that the test feed had a buoyancy of 6.23 cm/sec, durability of 1441 seconds, homogeneity level of 79.32%, and hardness level of 86.51%. Chemically, the feed contained 25.85% protein, 5.81% water, 9.90% ash, 4.84% fat, and 30% carbohydrates. After being tested on tilapia fingerlings, the self-made feed produced absolute weight and length growth, FCR, EPP, and SR of 11.56 g, 4.47 cm, 1.84, 54.17%, and 90%, respectively. These results indicated the potential use of self-made feed using local raw materials to reduce dependence on commercial feed.